Implications of water abstraction on the interconnected Central Rift Valley Lakes Sub-Basin of Ethiopia using WEAP - Goshime, D. W.; Haile, Alemseged Tamiru; Rientjes, T.; Absi, R.; Ledesert, B.; Siegfried, T. (Elsevier, 2021)
Study region: Central Rift Valley Lakes sub-basin, Ethiopia. Study focus: The competition for water is rapidly increasing in Central Rift Valley lakes sub-basin due to the combined effect of various water resources developments. However, the impacts of recent and future water resources development pathways on the water balance of the three interconnected lakes (i.e. Lake Ziway, Langano and Abiyata) are unknown. The Water Evaluation And Planning (WEAP) model was used to assess the development impacts on water resources of the interconnected lakes. We considered three development pathways that are, recent (2009–2018), short-term (2019–2028) and long-term development (2029–2038). Lake Ziway water inflows from six catchments were estimated using the Hydrologiska Byråns Vattenbalansavdelning (HBV) rainfall-runoff model. Crop water requirements for irrigation schemes were estimated by the CROPWAT model. New hydrological insights for the region: WEAP simulations show a total water demand of 102.3 Mm3 under the recent development pathway that increases by 46% and 118% for short-term and long-term development pathways, respectively. This will notably affect the water balance of the interconnected lakes and cause an unmet water demand of 47.9 Mm3 for the long-term (2028–2038). For Lake Ziway and Abiyata, water levels will decrease substantially to cause water scarcity in the long-term, and developments in Lake Ziway will significantly affect water storage in Lake Abiyata storages in Lake Abiyata. Overall, future developments will threaten the water resource of the interconnected lake system.